PEMBENTUKAN KARAKTER MANDIRI, TANGGUNG JAWAB DAN PERCAYA DIRI SISWA MELALUI KEGIATAN MUHADHOROH DI MI MAMBAUL ULUM CURAHPUTIH, JEMBER - Abdul Rohim Al Faizin; Mundir Mundir; Siti Rodliyah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
In the era of Society 5.0, character education is very necessary to help individuals control the impact of rapid technological advances on their development stage. One effective method in forming character is through habituation. Muhadharah activities are one of the educational activities carried out at MI Mambaul Ulum Curahputih to form students' independent character, responsibility and self-confidence. The aim of this research is to analyze the formation of students' independent, responsible and self-confident character through muhadharah activities at MI Mambaul Ulum Curahputih. This research uses a qualitative research approach with a case study type. This research was carried out at MI Mambaul Ulum Curahputih, Tegalwangi, Umbulsari, Jember, East Java, Indonesia. Data collection techniques using interviews, observation and documentation. To analyze the data using the descriptive model qualitative analysis method by Miles, Huberman and Saldana. To test the validity of the data obtained, researchers used data triangulation techniques, theories and methods. The results of this research show that the implementation of muhadharah activities at MI Mambaul Ulum Curahputih is divided into 4 stages, namely planning, preparation, implementation and evaluation. Through muahdarah activities, students are accustomed to being independent, responsible and confident in completing the tasks given. In forming independent character, responsibility and self-confidence through muhadharah activities, character formation is carried out in three stages, namely the knowledge, implementation and habituation stages